2011
DOI: 10.1099/jmm.0.036103-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic pulmonary blastomycosis with caspofungin

Abstract: Current practice guidelines recommend that pulmonary blastomycosis be treated with antifungal agents such as amphotericin B and itraconazole. Echinocandins are not recommended because of poor in vitro activity against Blastomyces dermatitidis and lack of supporting clinical data. We report a case of chronic pulmonary blastomycosis treated successfully with caspofungin. Case reportA 32-year-old male with no prior history of disease and working in construction presented with an insidious onset of right thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The authors do not advocate this strategy because of the minimal amount of drug target, β-(1,3)-glucan, in the cell wall of B. dermatitidis. 72,157 Adjunctive Therapy…”
Section: New Triazolesmentioning
confidence: 99%
“…The authors do not advocate this strategy because of the minimal amount of drug target, β-(1,3)-glucan, in the cell wall of B. dermatitidis. 72,157 Adjunctive Therapy…”
Section: New Triazolesmentioning
confidence: 99%
“…However, there have been no clinical studies that have demonstrated the inferiority of echinocandins compared to other antifungals for the treatment of C. parapsilosis infections 99) . For treatment of blastomycosis 100) , coccidioidomycosis 101) , and Pneumocystis pneumonia 79, 80) (type 3), though not approved nor recommended, it has been reported that echinocandins, alone or in combination, was effective. For therapy of mucormycosis (type 4), combination of lipid formulations of amphotericin B and echinocandins, though its mechanism is unknown, has often been used [102][103][104] and recommended as first-line or salvage therapy in some guidelines 97,105) .…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Thus, isavuconazole and posaconazole can be considered alternative agents for blastomycosis. Lastly, echinocandins should not be used due to poor in vitro activity and rare reported use with mixed results resulting in clinical failure [35,68,69].…”
Section: Alternatives To Standard Treatmentmentioning
confidence: 99%